Thermal conductivity of individual multiwalled carbon nanotubes - Khosravian, Narjes (2013)
Thermal conductivity of individual multiwalled carbon nanotubes (MWCNT) is measured using a pulsed photothermal reflectance technique. Intrinsic thermal conductivity of individual MWCNT with a diameter 150 nm and length 2 μm at room temperature is extracted to be 2586 W/mK. Individual MWCNT is surrounded by SiO2, so parallel resistor model is applied in which SiO2 supportive is treated as a conducting channel that transports heat in parallel with MWCNT.